THE EFFECT OF WORK STRESS AND EMOTIONAL INTELLIGENCE MEDIATION ON PERFORMANCE - Sari, Intan Kumala; Saputra, Febri (REVENUE: Jurnal Manajemen Bisnis Islam, 2022)
Rapid development Information technology brings enormous benefits to the progress of human civilization. The rise of online technology allows everyone to be more productive and efficient. One of the current applications of information technology is the development of online transportation using motorcycle taxis such as Gojek.This study aims to determine whether work stress and emotional intelligence affect performance, and whether emotional intelligence is able to mediate the relationship between the two.This study uses a quantitative approach. The research will be conducted on Gojek drivers in the city of Bandar Lampung, with 97 Gojek drivers as respondents of this research. Sampling in this study used a probability sampling technique, namely cluster sampling. Data collection was carried out by distributing questionnaires to Gojek drivers in Bandar Lampung City by google form. The analytical method used in this research is the method partial least squares structural equation modeling (PLS-SEM) and the use of SmartPLS software in data processing. The results showed that the higher the work stress experienced, it will reduce the level of emotional intelligence and a person's performance. In addition, the higher the level of emotional intelligence of a person, it will improve his performance as well.